Implementasi Teknologi Layanan Pelanggan BCA KCP Besuki Kabupaten Situbondo - Nabila Syahda Kamila; Nurul Holida (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
BCA KCP Besuki is located to the west of Besuki square, Besuki Village, Besuki District, Situbondo Regency, East Java 68356. The establishment of BCA KCP Besuki cannot be separated from the role of KCU Situbondo as the head office. Bank Central Asia is one of the largest banks in Indonesia which is divided into 12 (twelve) regional offices throughout Indonesia. The application of digital technology will follow economic theory which explains that technological progress leads to increased productivity and encourages company efficiency. An efficient and productive company will increase its ability to compete and dominate the market. The world of banking competition is very competitive so improving service quality must be carried out and always strived for. This is a real effort to gain competitive advantage and achieve customer satisfaction. Mobile banking, CS Digital, and E-Service, are banking services that can be accessed by customers very easily and very quickly. With the Mobile banking, CS Digital, and E-Service, facilities, every customer can make transactions very easily and very quickly at any time and in any branch. With service. Mobile banking, CS Digital, and E-Service, are expected to provide convenience, interest and benefits for customers in accessing the bank.